Germination and sporophyte frequency of two sympatric species of Blechnum (Blechnaceae) - López-Romero, Juan Manuel; Riaño, Karolina; Briones, Oscar (Instituto de Ecología, A.C., 2016)
Background and Aims: Light and water are resources that limit the germination and growth of vascular plants in forests and the establishment process significantly influence the species distribution. For this reason, we evaluated whether sympatric ferns Blechnum appendiculatum and B. schiedeanum (Blechnaceae) differ in habitat preference and if their germination requirements may help explain their distribution in a mountain mesophyllous forest.Methods: Spores were exposed to light quality, amount of light and water potential treatments. The frequency of sporophytes of both species and the proportion of light received in the forest was also recorded.Key results: It was found that both species did not germinate in darkness and few spores did so with far-red wavelength compared to white light. The spore sprout was promoted with the increase of light intensity, and 0.04 µmol m-2 s-1 light was sufficient so this was more than 60% in both species. The decrease in water availability reduced the germination, but B. appendiculatum showed greater ability to withstand water scarcity to -1.05 MPa. Blechnum schiedeanum was abundant in environments with relatively closed canopy while B. appendiculatum occurred more frequently on the forest border.Conclusions: Germination requirements were partially related to habitat preference of the species. Blechnum schiedeanum seems to be more shade tolerant than B. appendiculatum.